Seeing Islam as a Social Fact: Hermeneutic Approach to the Quran in Abu Zayd's Thought - Muhammad Yaufi Nur Mutiullah (Qur'an and Hadith Academic Society, 2023)
This study aims to discuss Nasr Hamid Abu Zayd's thoughts on the Quran as scripture. Using the type of literature study research, this article explains Abu Zayd's thoughts as contained in several of his writings. This study's findings state that Abu Zayd's argument that the Quran as a cultural product and cultural producer (muntaj tsaqafi and muntij tsaqafi) departs from Abu Zayd's approach, which sees Islam as a social fact. There is a big difference between Islam, studied as a social fact, and Islam, seen as a religious doctrine. Islam as a social fact demands objective and positive scientific work. Abu Zayd took a new approach to the Quran by shifting the direction of study from a vertical dimension to a horizontal dimension. The horizontal dimension referred to by Abu Zayd is the canonization in which the teachings of the Quran were spread gradually by the Prophet Muhammad. This article also concludes that Abu Zayd sees it as a text for studying the Quran. It is at this point that Abu Zayd uses a hermeneutic approach. It is at these two points that Abu Zayd said that his study of the Quran is based on the human aspect. What Abu Zayd means by studying the Qur'an, which departs from the human aspect with a horizontal dimension is also what is meant by Islam as a social fact in this article. In the order of writing, the article sequentially discusses the following points. The first part of this article reviews a brief biography of Abu Zayd, along with the social and political conditions that influenced his thinking. The second part explains the Quran as a text. And in the last section describes the Quran as a product as well as a cultural producer